QI at Barnet General Hospital: to make the AAU Hub a paperless, Sustainable Green project - Lauren Farber; Ratnadeep Ghadge (Future Healthcare Journal)
Introduction and aim: The adult assessment unit (AAU) hub at Barnet includes an ambulatory clinic and geriatric hot clinic, and was using a system of paper and folders for patient flow (Fig 1). This increased the workload for admin staff and delayed patient care, leading to higher operational costs and reduced efficiency.A well-established time-tested system and a high volume of patients in the AAU hub were noted to be obstacles for switching to an online system. Given that papers and folders could be lost, there was also a risk of patient confidentiality breaches.The study was undertaken with the aims of: 1. Making patient plans and reviews transparent; 2. Avoiding risks to confidentiality; 3. Improving communication between doctors and nurses; 4. Reducing paper consumption to a minimum. Methods: Cerner capability was used to eliminate unnecessary paperwork and coordinate patient data in real time. Surveys were undertaken pre and post rollout of the online system.Interventions were carried out in the form of teaching and training of doctors, admins and nurses. Posters were circulated via email and WhatsApp of the new patient flow system (Fig 2). These were also printed and put up in the triage room, admin desk and doctors room as a visible cue.Two trial runs carried out, the first on 6 March 2025 and the second on the 22 April 2025, followed by discussions about further changes before the final rollout. The final online system was rolled out on 22 April and has been running efficiently since then. Results: Results obtained from the surveys indicated that: 1. The ease of use of the online system was comparable to that of the pre-existing paper system, and all grades of staff were able to easily adapt to the new system with some training and guidance; 2. Risk to breach of confidentiality was reduced to nearly 0% from 50%; 3. Communication between nurses and doctors was clearer and timely with less ambiguity.; 4. Data accessibility and transparency improved from 46% to 87%.Results obtained from data collection showed that: 1. Paper consumption was reduced by 95% (40,000/year to 1,500/year) 2. Admin time saved was 2–3 h/day, saving £12,000–18,000/year (£16.73/h) 3. The clinic capacity doubled from 30 to 60 patients, with a reduction in average wait time to 10 min from 30 min. 4. Checkout rate increased from 65% to >95%, resulting in a reduction in the financial loss of nearly £100,000/year. Discussion: There was initial resistance to switching from a well-established paper system to the new online system. Initial survey and feedback from nurses and doctors was used to formulate plan for implementation of the new online system in a stepwise manner.Personalised teaching to admins, nurses and doctors was helpful to address individual queries and concerns. Given that everyone's interests were considered, the rollout was successful.Irrespective of their role, all staff (nurses, admins and doctors) played a crucial part in the success of this project. Everyone felt that they were having a positive impact on patient care and the environment. The role of patient flow was shared across staff and the end point was achieved with good teamwork.